Easily handling penicillin G acylase magnetic cross-linked enzymes aggregates: Catalytic and morphological studies - Kopp, Willian; Costa, Taciane P. da [UNESP]; Pereira, Sandra C.; Jafelicci, Miguel [UNESP]; Giordano, Roberto C. [UNESP]; Marques, Rodrigo Fernando Costa [UNESP]; Araujo-Moreira, Fernando M.; Giordano, Raquel L. C. (Elsevier B.V., 2014)
Biomolecules labeled with superparamagnetic nanoparticles can be selectively removed from complex reaction mixtures using an external magnetic field. Amino-functionalized superparamagnetic iron oxide nanoparticles (amino-SPION) were co-aggregated with penicillin G acylase and then cross-linked, generating magnetic cross-linked enzymes aggregates (M-CLEAs) that were quickly and efficiently recovered from the reaction medium by applying an external magnetic field. M-CLEAs and cross-linked enzymes aggregates (CLEAs) prepared under the same reaction conditions were characterized and compared. The best recovered activities were obtained for M-CLEAs prepared using polyethylene glycol 600 as precipitant and the most stable M-CLEA were obtained using tert-butanol. Successive penicillin G hydrolysis reactions were carried out using the same M-CLEA in a 50 mL reactor (3 reaction cycles), after the reactions the derivate was magnetically recovered without loss of activity demonstrating a total magnetic recovery. Line-scan energy dispersive X-ray spectroscopy showed that the amino-SPIONs were homogeneously dispersed within the structure of the M-CLEA. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Cross-linked enzymes aggregates; Superparamagnetic nanoparticles; Supramolecular complex; Magnetic recovery of enzymes; Penicillin hydrolysis